2019
DOI: 10.1021/acs.iecr.8b05693
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Technology Readiness Levels for the Chemical Industry

Abstract: Technology readiness levels (TRL) have received increasing recognition throughout academia, industry and policy-making as a tool for evaluating and communicating a technology's maturity.Conventional scales are unspecific to technologies as they aim at evaluating and comparing technologies combining different fields. Hence, they present vague descriptions which leave considerable room for interpretation and subjective choices. For the chemical industry, adaptions and specific criteria are needed for more compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 34 publications
1
76
0
1
Order By: Relevance
“…We apply the TRL specifications for the chemical industry, which provide detailed evaluation criteria based on an expert survey and therefore allow for a more objective form of evaluation. [ 22 ] Data availability and technology maturity go hand in hand: the TRL evaluation can be partly based on the evaluation of what data are available, and in return, a TRL signifies what data are available for assessment. We focus this assessment framework on early‐stage technologies from TRL 1 to TRL 4.…”
Section: Principles Of the Framework Designmentioning
confidence: 99%
See 3 more Smart Citations
“…We apply the TRL specifications for the chemical industry, which provide detailed evaluation criteria based on an expert survey and therefore allow for a more objective form of evaluation. [ 22 ] Data availability and technology maturity go hand in hand: the TRL evaluation can be partly based on the evaluation of what data are available, and in return, a TRL signifies what data are available for assessment. We focus this assessment framework on early‐stage technologies from TRL 1 to TRL 4.…”
Section: Principles Of the Framework Designmentioning
confidence: 99%
“…At TRL 1, basic research is translated to applications and general opportunities are identified. [ 22 ] For TRL 1, we suggest a macroscopic view, evaluating technology options in general with explorative concepts such as brainstorming or qualitative screening. For assessment at TRL 1, practitioners need to perform a literature study on existing observations of basic principles; including observations from own experiments is optional.…”
Section: Efferi Assessment Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology readiness levels (TRL) shown in Table 1 are used to indicate technological maturity and were initially introduced by the U.S. National Aeronautics and Space Administration in 1974. They were later adopted by the U.S. Department of Defense, European Space Agency, ISO 16290:2013 standard, and the European Union’s Horizon 2020 program [ 129 ].…”
Section: Translationmentioning
confidence: 99%